2017
DOI: 10.1001/jamapediatrics.2017.0124
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Autism Spectrum Disorders According to Period of Prenatal Antidepressant Exposure

Abstract: IMPORTANCE Several studies have examined the links between prenatal exposure to antidepressants and autism spectrum disorders (ASDs) in children, with inconsistent results, especially regarding the impact of the trimester of exposure. OBJECTIVE To perform a systematic review of the literature and a meta-analysis of published studies to assess the association between ASDs and fetal exposure to antidepressants during pregnancy for each trimester of pregnancy and preconception.DATA SOURCES PubMed, EMBASE, and Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 58 publications
3
67
0
3
Order By: Relevance
“…Evidence, both positive and negative, is mounting in relation to the role these risks play in the etiology of ASD. Several areas are now underpinned by relatively large bodies of evidence such as parental age and SSRI medication [58, 130132], while others lines of inquiry have generated relatively little specific evidence such as smoking and alcohol use [145, 146, 150154]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence, both positive and negative, is mounting in relation to the role these risks play in the etiology of ASD. Several areas are now underpinned by relatively large bodies of evidence such as parental age and SSRI medication [58, 130132], while others lines of inquiry have generated relatively little specific evidence such as smoking and alcohol use [145, 146, 150154]. …”
Section: Discussionmentioning
confidence: 99%
“…SSRIs cross the placenta barrier, potentially triggering a cascade of adverse effects including reduced serotonin uptake, reduced uterine blood flow, and hypoxia resulting in brain damage. A systematic review of the literature aiming to assess the association between ASD and fetal exposure to antidepressants during pregnancy, from preconception and across each trimester of pregnancy, included ten studies with six case–control studies (117,737 patients) in a meta-analysis [130]. Findings revealed a positive association between SSRI exposure and ASD, consistent across all trimesters (OR 1.81; 95% CI 1.49–2.20), which while partially mitigated by controlling for past maternal mental illness (OR 1.52; 95% CI 1.09–2.12) remained significant.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta‐analyses using four studies a significant association between first trimester SSRI exposure and ASD was reported (Brown et al, ), however the ability to account for confounding factors such as maternal mental illness and use of other psychotropic medication limited these findings. In another recent study Mezzacappa and colleagues (Mezzacappa et al, ) reported a significant association between increased ASD risk and maternal use of antidepressants during pregnancy. However, this association appeared to be more consistent when exposure occurred before conception rather than during pregnancy itself.…”
Section: Ssri Antidepressant Effectsmentioning
confidence: 95%
“…SSRIs are highly prescribed in pregnant women for mood disorders with prevalence of 5-13% (Cooper, Willy, Pont, & Ray, 2007). A recently published meta-analysis reported a significant case-control association between maternal antidepressant use and ASD risk in offspring, which remained when adjusted for maternal psychiatric history (Mezzacappa et al, 2017). Meta-analyzed cohort studies replicated the SSRI-ASD link, but not the independence from psychiatric history.…”
Section: Introductionmentioning
confidence: 99%